2022
DOI: 10.1111/liv.15207
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rifaximin on infections, acute‐on‐chronic liver failure and mortality in alcoholic hepatitis: A pilot study (RIFA‐AH)

Abstract: Background & Aims Alcoholic hepatitis (AH) is associated with a high incidence of infection and mortality. Rifaximin reduces bacterial overgrowth and translocation. We aimed to study whether the administration of rifaximin as an adjuvant treatment to corticosteroids decreases the number of bacterial infections at 90 days in patients with severe AH compared to a control cohort. Methods This was a multicentre, open, comparative pilot study of the addition of rifaximin (1200 mg/day/90 days) to the standard treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…In a randomized clinical trial of 32 patients with alcohol-related hepatitis, prophylactic antibiotic therapy with rifaximin for 4 weeks did not significantly improve inflammatory markers and amino acid measures compared with standard medical treatment . A case-control study of 21 patients with alcohol-related hepatitis treated with rifaximin reported a lower incidence of infection compared with 42 control patients at 90-day follow-up, but there was no survival benefit …”
Section: Discussionmentioning
confidence: 95%
“…In a randomized clinical trial of 32 patients with alcohol-related hepatitis, prophylactic antibiotic therapy with rifaximin for 4 weeks did not significantly improve inflammatory markers and amino acid measures compared with standard medical treatment . A case-control study of 21 patients with alcohol-related hepatitis treated with rifaximin reported a lower incidence of infection compared with 42 control patients at 90-day follow-up, but there was no survival benefit …”
Section: Discussionmentioning
confidence: 95%
“…Three studies, including two RCTs and one case-control study, were included in the final meta-analysis. [18][19][20] Of a total of 162 patients, 69% were male. Baseline study population characteristics, including median patient age, MELD, and MDF, as well as treatment regimens are reported in Tables 4 and 5.…”
Section: Resultsmentioning
confidence: 99%
“…In the non-rifaximin group, 18 out of the 42 patients developed a total of 26 infections, 8 of which progressed to sepsis, including 7 urinary tract infections, 6 spontaneous bacteremias, 5 spontaneous bacterial peritonitis, 5 pneumonias, 2 colitis, and 1 cellulitis. 18,20 90-day mortality. There was no significant difference in 90-day mortality rate between the rifaximin versus non-rifaximin group (RR: 0.743, 95% CI: 0.298-1.850, I 2 = 24%, P = 0.523) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…GR in hepatocytes likely has a major role in regulating neutrophil homeostasis via differentially regulating CXCL1, CXCL2, and CXCL8. A recent pilot study shows that co-treatment of sAH patients with GC and the antibiotic rifaximin is safe, with a reduction in liver-related complications and infections compared with a historical cohort [ 240 ]. The increase in the aldosterone/MR pathway is associated with increased alcohol drinking in patients with alcohol use disorders [ 241 ], and MR antagonists inhibit alcohol self-administration in rats [ 242 ].…”
Section: Summary and Perspectivesmentioning
confidence: 99%